Методичний підхід до оцінки готовності підприємства до реалізації інвестиційної стратегії - Якимчук, Тетяна Володимирівна (My University, 2015)
У статті представлено методичний підхід до оцінки готовності підприємства до реалізації інвестиційної стратегії. Методичний підхід ґрунтується на співставленні результатів виробничої, фінансової та інвестиційної діяльностей галузі та підприємства. Розраховуються інтегральні показники, які дозволяють порівняти достатність внутрішньої готовності підприємства до реалізації інвестиційної стратегії і вимоги зовнішнього середовища. Запропонований методичний підхід сприяє підвищенню ефективності управління інвестиційною стратегією підприємства шляхом виявлення та усунення недоліків у його господарській діяльності. A methodical approach of assessment of the enterprise's readiness to implement an investment strategy was presented in the article. The methodical approach is based on comparing the results of the production, financing and investment activities of the enterprise and industry. Types of activities take into account the interrelation between the investment and other functional strategies. The integral indicators are calculated and it allows comparing the adequacy of internal enterprise's readiness to implement the investment strategy and requirements of the environment. After calculation weaknesses of the enterprise can be identified and the management decisions can be offered to improve the selection and implementation of investment projects. The methodical approach contributes to improve the efficiency of the investment strategy management by identifying deficiencies and taking remedial action in the economic activities of the enterprises.
Keywords: інвестиційна стратегія; оцінка; фінансова складова; виробнича складова; управлінська складова; функціональна стратегія; управління; investment strategy; assessment; financial component; manufacturing component; administrative component; functional strategy; management; кафедра економіки праці та менеджменту